The Effective School Development in Remote Area; Case Study in MTs Sunan Kalijaga Sendang - Tri Prasetiyo Utomo (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2020)
The difference between urban and rural areas is of course very significant. These differences include economic, cultural, and social factors in the community that become their perspective and thinking paradigm. This situation will affect the need for education and educational awareness. This problem is caused by many factors, in addition to the aforementioned factors, it is also supported by the lack of public facilities and infrastructure, especially decent education services. This research aims to reveal that the lack of facilities and infrastructure in remote areas is not a major obstacle in establishing effective schools. This study uses a qualitative research method, by applying a field phenomenon approach study. Data collection techniques are carried out by in-depth interviews, observations, and other documents relevant to the development of effective schools. The results showed that effective schools in remote areas were developed in two stages, first, a process approach; includes strong principal leadership, building a good external school network, and a conducive school climate. Second, the target approach, which includes strengthening foreign culture, building religious culture, student discipline, and student achievement.